Alternative‐Ultrathin Assembling of Exfoliated Manganese Dioxide and Nitrogen‐Doped Carbon Layers for High‐Mass‐Loading Supercapacitors with Outstanding Capacitance and Impressive Rate Capability. (27th January 2021) - Jeong, Jae‐Min; Park, Seung Hwa; Park, Hong Jun; Jin, Se Bin; Son, Seon Gyu; Moon, Jong‐Min; Suh, Hoyoung; Choi, Bong Gill
Abstract: Manganese dioxide (MnO2 ) materials have received much attention as promising pseudocapacitive materials owing to their high theoretical capacitance and natural abundance. Unfortunately, the charge storage performance of MnO2 is usually limited to commercially available mass loading electrodes because of the significantly lower electron and ion migration kinetics in thick electrodes. Here, an alternatively assembled 2D layered material consisting of exfoliated MnO2 nanosheets and nitrogen‐doped carbon layers for ultrahigh‐mass‐loading supercapacitors without sacrificing energy storage performance is reported. Layered birnessite‐type MnO2 is efficiently exfoliated and intercalated by a carbon precursor of dopamine using a fluid dynamic‐induced process, resulting in MnO2 /nitrogen‐doped carbon (MnO2 /C) materials after self‐polymerization and carbonization. The alternatively stacked and interlayer‐expanded structure of MnO2 /C enables fast and efficient electron and ion transfer in a thick electrode. The resulting MnO2 /C electrode shows outstanding electrochemical performance at an ultrahigh mass loading of 19.7 mg cm −2, high gravimetric and areal capacitances of 480.3 F g −1 and 9.4 F cm −2 at 0.5 mA cm −2, and rapid charge/discharge capability of 70% capacitance retention at 40 mA cm −2 . Furthermore, asymmetric supercapacitor based on high‐mass‐loading MnO2 /C can deliver an extremely high energy of 64.2 Wh kg −1 at a power density of 18.8 W kg −1 in an aqueous electrolyte. Abstract : An efficient and high‐throughput fluid dynamics process is developed for the preparation of ultrathin and nitrogen‐doped carbon‐coated MnO2 nanosheets, leading to an outstanding pseudocapacitance of 480.3 F g −1 and 9.4 F cm −2 at an ultrahigh mass loading of 19.7 mg cm −2, an impressive rate capability of 70% capacitance retention, and excellent long‐term stability with 90% capacitance retention over 10 000 cycles.